PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP LOYALITAS KONSUMEN MAJALAH SWA MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Kasus di DKI Jakarta) - Mohammad Fahmi Shodiq; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
The advanced development of technology in this era has caused magazines to slowly being left by their readers. The purpose of this research is to explain the influence of product quality and advertisement towards the loyalty of SWA magazine costumer’s trough customer satisfaction as intervening variable. The result of multiple linear regression analysis shows that the product quality and advertisement variable has positive impact towards costumers satisfactions, and between two variables product quality and advertisement there’s only one variable with positive impact towards costumers loyalty which is the advertisement variable, whereas the product quality variable has resulted in negative impact. The result of the research shows that there’s positive and significant impact trough each variables product quality and advertisement towards costumers satisfaction, negative impact and insignificancy was found between advertisement variable to costumers satisfaction variable, and there was positive and significant impact between costumer’s satisfactions towards costumer’s loyalty.The conclusion is according to most of the respondents, the product quality of SWA magazine is already good, the satisfaction is high enough, and so does the loyalty of the magazine costumers. Suggestions that can be given trough this research is for the magazine to keep the loyalty of its costumers then the magazine need to increase the quality of its product, increase the quality of the advertisement, and maintain the good relations with its costumers because to gain new costumers would need more energy and cost than keeping the already existed costumers.